Download presentation

Presentation is loading. Please wait.

Published byGregory Owen Pearson Modified over 8 years ago

2
GRAPHING LINEAR FUNCTIONS

3
Graphing Straight Lines This presentation looks at two methods for graphing a line. 1.By finding and plotting points 2.Using the gradient and the y - intercept where y = mx + b m is the gradient b is the y-intercept

4
1.Graphing Straight Lines by plotting points y = 2x – 1 Choose values for x and find the corresponding value for y x = 1, y = 2(1) - 1 = 1 x = 2, y = 2(2) - 1 = 3 x = -1, y = 2(-1) - 1 = - 3 Connect the points This information is often presented in table form x y 1 1 2 3 –1 –3

5
y = – x + 2 Choose values for x and find the corresponding value for y x = 1, y = -(1) +2 = 1 x = 2, y = -(2) +2 = 0 x = -1, y = -(-1) +2 = 3 x = 3, y = -(3) +2 = -1 Connect the points 1.Graphing Straight Lines by plotting points

6
2.Graphing Straight Lines by using the gradient and the y -intercept y = 2 x – 3 m = y- intercept = 2 – 3 Place a point at the y -intercept A gradient of 2 is a rise of 2 over a run of 1 This gives us the point (1, –1) Connect the points

7
2.Graphing Straight Lines by using the gradient and the y -intercept y = – 4 x + 2 m = y- intercept = – 4 2 Place a point at the y -intercept A gradient of –4 is a drop of 4 over a run of 1 This gives us the point (1, –2) Connect the points

8
2.Graphing Straight Lines by using the gradient and the y -intercept y = – x – 3 m = y- intercept = – 1 – 3 Place a point at the y -intercept A gradient of –1 is a drop of 1 over a run of 1 This gives us the point (1, –4) Connect the points

9
2.Graphing Straight Lines by using the gradient and the y -intercept m = y- intercept = 2 Place a point at the y -intercept This gives us the point (3, 4) Connect the points A gradient of is a rise of 2 over a run of 3

10
Re-arranging equations to read the gradient and the y -intercept Remember the general form of a straight line is y = mx + b Example 1 Subtract x from both sides Rearrange so that the x term is first Therefore, the gradient is – 1 and the y -intercept is 7.

11
y = mx + b Example 2 Subtract 3 x from both sides Rearrange so that the x term is first Therefore, the gradient is – 3 and the y -intercept is – 2

12
y = mx + b Example 3 Subtract 4 x from both sides Rearrange so that the x term is first Therefore, the gradient is 4 and the y -intercept is – 1 Multiply both sides by – 1

13
y = mx + b Example 4 Add x to both sides Rearrange so that the x term is first Divide both sides by 2 Therefore, the gradient is and the y -intercept is 2.5

14
y = mx + b Example 5 Add 2 x to both sides Rearrange so that the x term is first Divide both sides by 3 Therefore, the gradient is and the y -intercept is

15
y = mx + b Example 6 Subtract 4 x from both sides Rearrange so that the x term is first Divide both sides by 2 Therefore, the gradient is – 2 and the y -intercept is 3

16
We wish to thank our supporters:

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google